MENINGKATKAN KEMAMPUAN PENJUMLAHAN MELALUI MEDIA MOBIL-MOBILAN BAGI ANAK TUNAGRAHITA SEDANG - Delli - Elfira (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background by the problems which the child is experiencing difficulty in mental retardation count operations of addition, children can not solve sums in mathematics. This study aims to improve children's ability in mathematics, especially up to a maximum sum of the results by using the numbers five cars.The methodology that researchers use is the single sabject research study by the research design is design A - B. Data analysis techniques are used based on the observation data in the form of visual analysis of the graph. The results were analyzed with an analysis of the conditions and analysis between conditions. Long baseline condition 6 times and 7 times the intervention condition. Direction of trend data indicates a steep line means there is a change in the ability of the sum of numbers in children towards more good. pada X baseline conditions increase the value 0% -30% and the intervention condition increased its value 50% -90%. So the rate of change in the baseline condition (30%) and the rate of change in the intervention condition (40%). From the results of the data acquisition is concluded that the media in the form of semi-concrete cars can be used to improve the ability of the sum of numbers in child mental retardation were class III. Suggested for classroom teachers or math teachers to use media in the form of semi-concrete toy cars to children mental retardation is in teaching counting numbers.